Supporting carers to manage pain medication in cancer patients at the end of life: A feasibility trial. (January 2018) - Latter, Sue; Hopkinson, Jane B; Lowson, Elizabeth; Hughes, Jane A; Hughes, Jacki; Duke, Sue; Anstey, Sally; Bennett, Michael I; May, Carl; Smith, Peter; Richardson, Alison
Background: Carers of people with advanced cancer play a significant role in managing pain medication, yet they report insufficient information and support to do so confidently and competently. There is limited research evidence on the best ways for clinicians to help carers with medication management. Aims: To develop a pain medicines management intervention (Cancer Carers Medicines Management) for cancer patients' carers near the end of life and evaluate feasibility and acceptability to nurses and carers. To test the feasibility of trial research procedures and to inform decisions concerning a full-scale randomised controlled trial. Design: Phase I-II clinical trial. A systematic, evidence-informed participatory method was used to develop CCMM: a nurse-delivered structured conversational process. A two-arm, cluster randomised controlled feasibility trial of Cancer Carers Medicines Management was conducted, with an embedded qualitative study to evaluate participants' experiences of Cancer Carers Medicines Management and trial procedures. Setting: Community settings in two study sites. Participants: Phase I comprises 57 carers, patients and healthcare professionals and Phase II comprises 12 nurses and 15 carers. Results: A novel intervention was developed. Nurses were recruited and randomised. Carer recruitment to the trial was problematic with fewer than predicted eligible participants, and nurses judged a high proportion unsuitable to recruit into the study. Attrition rates following recruitment were typical for the study population. Cancer Carers Medicines Management was acceptable to carers and nurses who took part, and some benefits were identified. Conclusion: Cancer Carers Medicines Management is a robustly developed medicines management intervention which merits further research to test its effectiveness to improve carers' management of pain medicines with patients at the end of life. The study highlighted aspects of trial design that need to be considered in future research.